2007
DOI: 10.1111/j.1365-3083.2007.01936.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of HLA genes with Ankylosing Spondylitis in Han Population of eastern China

Abstract: Ankylosing spondylitis (AS) is a chronic inflammatory disorder with a multifactorial genetic basis. HLA‐B27 was reported with the greatest susceptibility to AS but did not act alone. The aim of this study was to search for other gene(s) associated with AS independently of HLA‐B27 using 13 microsatellite markers spanning 1.5 Mb from locus TAP1 to HLA‐Cw and a single‐nucleotide polymorphism marker within NFκBIL1 gene promoter. Genotyping for microsatellites was performed in 175 AS patients of eastern Chinese and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The observed significantly higher frequency (before correction) of the STR_MICA-A5 allele among patients [19,20]. In the end, it is of interest to note that, although this microsatellite has shown association with numerous diseases in studies reported so far, we have not observed any correlation between D6S273 and TGCT [20].…”
Section: Resultsmentioning
confidence: 70%
“…The observed significantly higher frequency (before correction) of the STR_MICA-A5 allele among patients [19,20]. In the end, it is of interest to note that, although this microsatellite has shown association with numerous diseases in studies reported so far, we have not observed any correlation between D6S273 and TGCT [20].…”
Section: Resultsmentioning
confidence: 70%
“…It has been confirmed that HLA genes are involved in enhancing genetic susceptibility to AS, and the function of KIR on effecter cells is highly dependent on the HLA molecules expressed on target cells (Boyton & Altmann, 2007; Carter et al. , 2007; Fang et al. , 2007).…”
Section: Discussionmentioning
confidence: 96%
“…Consensual diagnosis of AS in each patient was made according to the modified New York criteria [24] by two independent rheumatologists. The patients' pelvic and lumbosacral spine radiographs were read by a radiologist and a third rheumatologist as previously described [25].…”
Section: Methodsmentioning
confidence: 99%